Comparative analysis of increasing CBR value of soil with adding bamboo leaf ash - Woelandari Fathonah; Dwi Esti Intari; Enden Mina; Rama Indera Kusuma; Eryani Siti Maryam (Jurnal Teknika, 2021)
Consider the importance of the subgrade strength in road building since its strength impacts the soil's performance in absorbing the load on it. One of the efforts to improve the subgrade, which has a low bearing capacity, is by stabilizing the soil using bamboo leaf ash. This study aims to analyze the increase in CBR value with the addition of bamboo leaf ash. The analysis results showed that bamboo leaf ash from the furnace combustion process with a temperature range of 800oC-1000oC produced a higher CBR strength value than bamboo leaf ash from ordinary combustion without a furnace. The result is the higher silica content in the bamboo leaf ash from the furnace combustion process. This silica has pozzolanic and self-cementing properties, namely the ability to harden and increase strength when reacted with water. The addition of bamboo leaf ash with ordinary burning resulted in the optimum CBR value at seven days of curing of 13.1% at 10% bamboo leaf ash variation. At the same time, bamboo leaf ash with Furnace combustion resulted in optimum CBR values of 34.99% and 38.21% at 6% variation of bamboo leaf ash. Dalam konstruksi jalan mempertimbangkan nilai kekuatan tanah dasar, karena nilai kekuatan tanah dasar mempengaruhi performa tanah dalam menerima beban di atasnya. Salah satu upaya yang dapat dilakukan untuk memperbaiki tanah dasar yang memiliki daya dukung rendah yaitu dengan cara stabilisasi tanah menggunakan abu daun bambu. Penelitian ini bertujuan untuk melakukan analisa peningkatan nilai CBR dengan penambahan abu daun bambu. Hasil analisa menunjukkan bahwa abu daun bambu dari proses pembakaran furnace dengan range suhu 800oC-1000oC menghasilkan nilai kekuatan CBR lebih besar dibandingkan dengan abu daun bambu dari pembakaran biasa tanpa furnace. Hal ini disebabkan karena adanya kandungan silika yang lebih tinggi yang ada pada abu daun bambu dari proses pembakaran furnace. Silika ini memiliki sifat pozzolanic dan self cementing yaitu kemampuan untuk mengeras dan meningkatkan kekuatan jika bereaksi dengan air. Penambahan abu daun bambu dengan pembakaran biasa  menghasilkan nilai CBR optimum pada pemeraman 7 hari sebesar 13,1% pada variasi abu daun bambu 10%. sedangkan abu daun bambu dengan pembakaran Furnace menghasilkan nilai CBR optimum sebesar 34,99% dan 38,21% pada variasi abu daun bambu 6%.